PENGARUH MEDIA AUDIO VISUAL TERHADAP MAHARAH AL-KITABAH - Almannah Wassalwa Salwa; Masykuri Masykuri; Hamidatul Iflah (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2021)
This research to find out if audio visual media to writing skills in grade V students Mi Miftahul Ulum The use of audio visual media has a very important role that is: can provide many benefits as long as teachers play an important role in the learning process, in the study more focused on learning Arabic language in class V MI Miftahul Ulum researchers use case studies of the influence of audio visual media in maharoh kitabah which currently uses audio visual as a learning medium, in use of course there is a very good influence and not in arabic language learning. And can be seen from the average value of maharoh kitabah using Audio Visual learning media in grade V, maximal values reached 90 while the average class V was 77.4 while based on thitung = 2,552and ttabel at ά= 5% and dF= 25 = 0.413 therefore t count ≥ t table this indicates that 2,552 ≥ 0.413.